2012
DOI: 10.1093/cvr/cvs366
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase activation contributes to reduced connexin43 and development of atrial arrhythmias

Abstract: JNK activation contributes to Cx43 reductions that promote development of AF. Modulation of JNK may be a potential novel therapeutic approach to prevent and treat AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
96
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 31 publications
13
96
0
Order By: Relevance
“…In HL-1 cell cultures, JNK activation by anisomycin treatment led to reduction of connexin 43, which impaired cell-cell communication between atrial myocytes and ultimately prompted the development of atrial arrhythmias. These effects were prevented by the specific JNK inhibitor, SP600125 13 . An in vivo study in rabbits showed that treatment with anisomycin reduced connexin 43 by 34% and increased pacing-induced atrial arrhythmias 13 .…”
Section: Cell-cell Junction Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In HL-1 cell cultures, JNK activation by anisomycin treatment led to reduction of connexin 43, which impaired cell-cell communication between atrial myocytes and ultimately prompted the development of atrial arrhythmias. These effects were prevented by the specific JNK inhibitor, SP600125 13 . An in vivo study in rabbits showed that treatment with anisomycin reduced connexin 43 by 34% and increased pacing-induced atrial arrhythmias 13 .…”
Section: Cell-cell Junction Formationmentioning
confidence: 99%
“…These effects were prevented by the specific JNK inhibitor, SP600125 13 . An in vivo study in rabbits showed that treatment with anisomycin reduced connexin 43 by 34% and increased pacing-induced atrial arrhythmias 13 . Collectively, these studies suggest that there is an intracellular link between stress-induced JNK signaling pathway and GJ function, ultimately affecting intercellular communication and cellular behavior 62 …”
Section: Cell-cell Junction Formationmentioning
confidence: 99%
“…3. Calculate action potential or calcium transient conduction velocity (CV) vectors on the AT matrix using the vector field analysis method as previously described with minor modifications 12,18 . 1.…”
Section: Dual Channel Optical Mappingmentioning
confidence: 99%
“…1. Calculate the CV vector of a data channel relative to its surrounding AT data points (5 × 5 neighboring averaged data channels) to simulate a smooth polynomial surface of activation times (AT surface) using a least-square algorithm within the MATLAB program 12,18 . 2.…”
Section: Dual Channel Optical Mappingmentioning
confidence: 99%
See 1 more Smart Citation